Incidencia de la información y comunicación en el clima organizacional de los servidores públicos del Gobierno Autónomo Descentralizado del cantón Chone - Salavarría Alvarado, José Leandro (2023)
This study was developed with the objective of evaluating the impact of information and communication management on the organizational climate of public servants of the Autonomous Decentralized Government in Chone canton (GAD Chone), for the proposal of an improvement plan. Information collection methodologies such as interviews and surveys were used, which were analyzed for reliability using Cronbach's Alpha test and a descriptive analysis of the relationship between variables was used to determine their relationship. The results show shortcomings in aspects such as inadequate management of communication and information processes, the objectives and goals of the communication and information processes do not correspond to the institutional objectives, lack of training in the management of information systems, and lack of motivation and job satisfaction programs. Regarding the association of the variables, there is a certain association between information and communication management and the organizational climate of the public servants of the GAD Chone. If the inconsistencies detected in this study are maintained, the delivery of services of the GAD Chone to its users would be affected in a certain way, making it unavoidable to adopt the corrective actions proposed in this research.